A case study of extreme rainstorm in northern Xinjiang under the influence of large-scale circulation and topography - Li, Jiangang; Li, Boyuan; Jiang, Cailian; Jiang, Yufei; Zhang, Jinru; Yang, Lianmei; Li, Na (Frontiers in Earth Science, 2025)
IntroductionHeavy rainfall events in Northern Xinjiang are primarily influenced by westerly systems, exhibiting strong extremity, which exacerbate secondary disasters. Meteorologists have conducted in-depth research on the trigger mechanisms, atmospheric backgrounds, meso- and microscale features, forecasting and warning techniques and environmental impacts of heavy rainfall events. Based on the automated weather station data, FY-4A satellite products, ECWMF model sounding data, NCEP-FNL and ERA5 reanalysis datasets, this study analyzes the environmental field characteristics of an extreme regional heavy rainfall event in Northern Xinjiang from August 7–9, 2023.MethodsThe heavy rainfall and short-term heavy rainfall were defined according to Xinjiang local precipitation standards, reanalysis datasets were primarily used to circulation patterns, water vapor transport, thermodynamic conditions and etc. Satellite products were utilized for cloud-top brightness temperature and water vapor convergence monitoring and analysis.ResultsThe results indicated that the heavy rainfall occurred under the circulation background of the eastern-type South Asian High. Influenced by the upstream European blocking high and downstream East Siberian ridge, the West Siberian trough merged with the Central Asian trough. Shortwave troughs propagating eastward ahead of this merged system continuously entered Northern Xinjiang, interacting with a strong and persistent low-level southwest jet stream convergence zone to trigger widespread heavy rainfall. Atmospheric stratification characterized by warm lower layers and cold upper layers, mesoscale convergence induced by low-level wind shear lines, and the presence of high-energy zones facilitated the release of substantial convective unstable energy. This triggered the rapid development and maintenance of Meso-β-scale convective cloud clusters, resulting in localized short-duration precipitation. Water vapor was primarily transported via the dominant western channel, supplemented by the eastern channel. Stable synoptic systems enabled significant water vapor to reach the heavy rainfall area in advance. The western boundary contributed to full-layer water vapor input, while the southern boundary provided mid-to-upper-level input, leading to increased water vapor flux, enhanced convergence, and prolonged saturation. Influenced by local topography, low-level wind convergence, and a dual-center vertical velocity and divergence configuration with a forward-tilted structure rapidly intensified precipitation.DiscussionThis study reveals that the cause of the heavy rainfall event in northern Xinjiang is the synergy of multi-scale systems under the background of abnormal circulation in Central Asia: the eastward-moving South Asian High (SAH) drives the southwest jet stream to extend southward, and in combination with the European blocking high (584-588 dagpm), it prompts the split of the Central Asian trough and the eastward movement of the short-wave trough. The rainstorm area shows a vertical structure of “cold above and warm below”, strong vertical wind shear and high CAPE value (>2500 J/kg), triggering deep convective cloud clusters with TBB ≤ -40°C. An innovative discovery of the double-channel water vapor convergence mechanism upstream and downstream is made, and combined with the uplift of the Altai Mountains, the water vapor flux and convergence intensity in front of the mountains are significantly higher than those of historical events. Satellite data verify its monitoring potential and resolution limitations in radar blind areas. This event confirms that the rapid eastward movement of the short-wave trough and the terrain-triggered mesoscale convection are the key factors causing disasters, emphasizing the need to establish a refined early warning system for mountain floods.